A Survey of Burnt Areas in Bwindi Impenetrable and Mgahinga Gorilla National Parks, S. W. Uganda The Fires Of 2000 - Kasangaki, Aventino; Babaasa, Dennis; Bitariho, Robert; Mugiri, Ghad (Institute of Tropical Forest Conservation, 2001)
Fire has been one of the main management challenges and is considered one of the major long-term threats to forest biodiversity in Bwindi Impenetrable and Mgahinga Gorilla National Parks. In June, July and August 2000 fire outbreaks occurred the two parks. During September 2000 we carried out a survey of the burnt areas, which aimed at documenting the burnt sites and extent of damage caused by the fires. This was done as part of a long term monitoring programme to advise park managers about what could be done to prevent, halt or decrease incidences of fire outbreaks. The results show that approximately 0.2 square kilometers constituting 0.05% of the total park area was affected by fire in Bwindi Impenetrable National Park. The area affected was significantly smaller than that burnt in 1999 (2.64 square kilometers, 0.8% of park area); there has been a significant reduction in fire incidences in Bwindi in 2000 that we have attributed to the difference in the number of ‘rainy days’ in the ‘North sector’ and Buhoma and Ruhija, improved park boundary maintenance and increased sensitization of communities surrounding the park. However, the total numbers of ‘rainy days’ during the months of May to September were not significantly different between 1999 (139 ‘rainy days’) and 2000 (127 ‘rainy days’). In Mgahinga Gorilla National Park, 0.1 square kilometers constituting 0.3% of the Park area was affected by fire. However, we have no previous with which to compare 5 these estimates. In both parks illegal honey collectors caused most fires with a few spreading from community agricultural fields. On a positive note, the communities’ response to putting out fires was almost 100%. This shows an improved attitude of the communities towards protected areas. Given the fact that fire has become a regular component of the disturbance regime in the two parks, we recommend preventive measures such as public education and good public relations between parks and local communities, instituting and enforcing legislation on regulations for lighting fire in the park, establishment of early warning systems and the establishment and maintenance of a clear park boundary. We further advocate for the provision and maintenance of appropriate equipment and training of park staff in fire suppression measures. Lastly, since illegal honey collectors caused most fires, we recommend that park staff and all stakeholders in the management of the two Parks intensify sensitization of the communities on the dangers of fire in protected areas.
Keywords: Burnt Areas; Bwindi Impenetrable; Mgahinga Gorilla